GEOMETRIC SHAPE OF FURNITUREFAMILY ROOM - Didiek Prasetya (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
The creation of this work of art is to design furniture making family room by applying a geometric shape as an idea or a reference shape, such as squares, triangles, circles and rectangles, because of the geometric shape is a shape that tends to have properties with the times to form a line that is strong, firm, hard, simple, and modern impression which does not want the order or complex shapes.This family room furniture making use of materials such as plywood blockboard and metals such as stainless steel. Techniques used in furniture pembutan family room is a technique carpentry or often referred to as engineering work bench and using welding techniques. The tool used was semi masinal tools (hand machine) and manual. Finishing applied is finishing tacon in red, black and silver.The basic idea of making furniture geometric-shaped living room is transformed into an alternative sketch, sketch elected, and working drawings. The basic idea visualized in 3-appointed with a variety of shapes. 1) TV shelf with a rectangular shape, a length of 150 cm, width 50 cm, and a height of 55 cm. This TV stand can hold many items, such as TV, VCD player, tape recorder, a collection of CDs, books and magazines. 2) Console table with triangular shapes to form elongated leaves his desk, a length of 90 cm, 30 cm wide and 82 cm high. The function of this console table is a decorative table, filling the long side wall of the family room and a shelf decoration. 3) The clock square with angular size of 34 cm, 4.5 cm thick and wide cross-section of winder diameter of 25 cm. This wall clock functions as a time to decorate the room and placed on a wallKeywords:Geometric shape, Furniture, Family Room